Control of Culex quinquefasciatus and Cx. saltanensis (Diptera: Culicidae) with Bacillus thuringiensis israelensis in wastewater treatment lagoons - Zequi, João Antonio C.; dos Santos, Fernando Pereira; Lopes, José (Revista Colombiana de Entomologia, 2014)
Industrial or urban wastewater treatment lagoons accumulate nutrients, which allows the proliferation of Cx. quinquefasciatus, vector of the etiologic agent of filariasis, and of Cx. saltanensis, vector of the protozoan causing malaria in chickens. The goal of this study was to evaluate the effectiveness and persistence of Aquabac® XT 1,200 UTI/ mg, Teknar® 3,000 AAU/mg, and Vectobac® AS 1,200 UTI/mg; these products are liquid formulations whose active principles are crystals produced by Bacillus thuringiensis israelensis. Products were tested in two wastewater treatment lagoons of a meat cold-storage facility. The lagoons measured 1,419 m2 and 736 m2, and received concentrations of 1 and 2 litres/hectare of each product, with three replicates each. Water pH, conductivity, oxygen and temperature were measured at each collection. Cx. quinquefasciatus and Cx. saltanensis were found in both lagoons. One litre/hectare concentration controlled 70 to 80% of the larvae in 24 and 48 hours, respectively; two litres/hectare concentration showed the best results, controlling 86 to 99% of the immature mosquitoes, with the highest efficiency observed at 48 hours. None of the products affected water quality according to the abiotic parameters examined. As a result, all products tested efficiently controlled these Culicidae under the local breeding conditions but had low persistence, with seventh-day larval indexes being similar to those recorded before application of the products. Weekly applications are recommended. © 2014 The American Society for Cell Biology.
Control de Culex quinquefasciatus y Cx. saltanensis (Diptera, Culicidae) con Bacillus thuringiensis israelensis en lagunas de aguas residuales
Keywords: Bacillus Thuringiensis Serovar Israelensis; Culex Pipiens Quinquefasciatus; Culicidae; Diptera